2018
DOI: 10.3390/sports6010001
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Month Effects of a Ketogenic Diet on Body Composition, Blood Parameters, and Performance Metrics in CrossFit Trainees: A Pilot Study

Abstract: Adopting low carbohydrate, ketogenic diets remains a controversial issue for individuals who resistance train given that this form of dieting has been speculated to reduce skeletal muscle glycogen levels and stifle muscle anabolism. We sought to characterize the effects of a 12-week ketogenic diet (KD) on body composition, metabolic, and performance parameters in participants who trained recreationally at a local CrossFit facility. Twelve participants (nine males and three females, 31 ± 2 years of age, 80.3 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 25 publications
2
79
2
3
Order By: Relevance
“…This implies that KT would have increased the FFM-to-FM ratio in our patients, similar to our previous findings [16]. These findings are consistent with studies conducted in exercising individuals where short-term KDs resulted in FM loss while maintaining lean mass and performance [3943]. Since most of our subjects did not exercise, a contribution of exercise-stimulated muscle protein synthesis can be ruled out asan explanation for the observed maintenance of SMM, and again the anti-catabolic effects of ketosis and/or anabolic effects of the supplemented essential amino acids may have contributed to the maintenance of SMM despite lower insulin levels and weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that KT would have increased the FFM-to-FM ratio in our patients, similar to our previous findings [16]. These findings are consistent with studies conducted in exercising individuals where short-term KDs resulted in FM loss while maintaining lean mass and performance [3943]. Since most of our subjects did not exercise, a contribution of exercise-stimulated muscle protein synthesis can be ruled out asan explanation for the observed maintenance of SMM, and again the anti-catabolic effects of ketosis and/or anabolic effects of the supplemented essential amino acids may have contributed to the maintenance of SMM despite lower insulin levels and weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…However, the KD group was instructed to consume foods ad libitum with a maximum of 50 g of carbohydrates per day, and reported decreasing energy intake bỹ 400 cal across the study period. More recently, Kephart et al [41] showed decreases in DXA-derived lower limb FFM and a decrease in vastus lateralis muscle thickness assessed by ultrasound when consuming a KD over a 12-week RT. The nutritional intervention of this study did not consider specific values of total calories or macronutrients used per g•kg − 1 •d − 1 , impairing the ability to estimate whether participants were in a state of energy deficiency or surplus.…”
Section: Discussionmentioning
confidence: 99%
“…In the area of exercise performance, there is a newfound interest in ketogenic diets. On one hand, ketogenic LCHF diets offer opportunities to induce weight loss and improve body composition, as reported recently [10][11][12]. This may increase relative, but not absolute, power due to decreased body weight, which can be important in situations when the ratio of lean to adipose body mass is crucial for performance.…”
Section: Introductionmentioning
confidence: 95%